Costa Rican Press and Highlights of the Second World War (1939-1945) - Vega Jiménez, Patricia (2019)
The objective of this text is to analyze the way in which the Diario de Costa Rica treated the main events of World War II between 1939 and 1945. The 14 fundamental moments were selected: the invasion of Poland, the declaration of war of France and England, the German invasions to the north and east of Europe, the fall of Paris to the Germans, the armistice and occupation of France, the invasion of Russia, the attack on Pearl Harbor, the landing and battle of Normandy, the liberation of Paris, the death of Mussolini, the capitulation of Germany and the atomic bombing of Hiroshima and Nagasaki. Methodologically, these facts were reported in high-level academic studies and contrasted with what was pointed out by the newspaper. The result is an obvious misrepresentation of the information that also came biased by the filter of the Associated Press, based in the United States and the only international source that the newspaper had.